Measuring the attitudes of the Iraqi public towards the public relations practices of - Ali Jabbar Al-Shammari / Laith Sabbar Jaber ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
This research attempts to show the importance and role of public relations for state institutions in general and for specialized organizations in particular in spreading awareness and forming trends about democratic practices in Iraq through the researcher’s reliance on a survey of the Iraqi public to find out its attitudes towards democracy indicators by being exposed to public relations programs and activities in government institutions concerned with publishing those practices, where the research results showed that 78.8% of the respondents do not have a party affiliation, in addition to the “social networking sites on the Internet” category, with a mean of 3.61 in the public’s quest for information on democratic practices. , While most respondents agreed to a large extent that “public relations programs did not succeed in forming a perception that democratic practice applied the principle of equal opportunities for all citizens to obtain public jobs in the state.” Research recommendations: The researcher recommends that the results of this study should be generalized The study on the general public, political parties and the media as part of the education process on democratic practices, and the researcher reached to build a real scale to measure the The practices of democracy in Iraq are based on “many requirements and indicators derived from the levels of political, social and economic development of the country, and in diagnosing democratic practices accurately and objectively, away from political and ideological positions.” Therefore, the researcher recommends the concerned parties to review it and benefit from its results to evaluate democracy in Iraq in other years.DOI /10.54633/2333-021-042-029